Predicting the benefits of type-2 targeted anti-inflammatory treatment with the prototype OxfoRd Asthma attaCk risk scaLE (ORACLE) - Couillard Castonguay, S; Do, WI; Beasley, R; Hinks, T; Pavord, I (European Respiratory Society, 2022)
The prototype ORACLE scale based on two simple measures of type 2 airway inflammation (blood eosinophils and FENO) quantifies the excess risk conferred by raised biomarkers that is removed by type-2 anti-inflammatory treatment in trial populations